2020
DOI: 10.3390/ijms21030751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bortezomib on Global Gene Expression in PC12-Derived Nerve Cells

Abstract: Peripheral neuropathy is one of the main side-effects of novel therapeutics used in oncohematological diseases, but the molecular basis underlying its development and progression as well as neurotoxicity mechanisms induced by the use of these therapeutics are still not fully elucidated. The aim of this study was to demonstrate the effect of bortezomib on global gene and miRNA expression on PC12-derived nerve cells. Microarray analysis showed that expression of 1383 genes was downregulated at least two fold and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Affymetrix miRNA 4.1 Array Stripes (Affymetrix, Santa Clara, CA, USA) were used for study and performed in n ¼ 3 technical replicates for each miRNA probe. Microarrays were made and analyzed according to the methods described in the previous articles [16,17].…”
Section: Mirna Analysismentioning
confidence: 99%
“…Affymetrix miRNA 4.1 Array Stripes (Affymetrix, Santa Clara, CA, USA) were used for study and performed in n ¼ 3 technical replicates for each miRNA probe. Microarrays were made and analyzed according to the methods described in the previous articles [16,17].…”
Section: Mirna Analysismentioning
confidence: 99%
“…The alternative pathway of complement activation is associated with many autoimmune diseases, such as arthritis and age-related macular degeneration [ 48 ]. Levin et al demonstrated in a mouse model an increase in proteins in the complementary system including properdin and factor D, both in the peripheral and central nervous system, during neuropathic pain [ 49 ]. In our study, we were the first to demonstrate an increase in the expression of genes regulating the complement system such as CFP encoding properdin and CFD encoding Factor D in patients with neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, miR-152-3p was discovered to modulate cell proliferation and invasion by targeting forkhead box F1 (FOXF1) in keloid fibroblasts [ 48 ]. The miR-152-3p/Gadd45 correlation is also investigated in PC12-Derived nerve cells [ 49 ]. To explore the downstream molecule of miR-152-3p, mRNAs binding with miR-152-3p were predicted using the starBase, and DDX6 was finally selected for further study due to its increased expression mediated by miR-152-3p inhibition in cells.…”
Section: Discussionmentioning
confidence: 99%